2011
DOI: 10.1021/jf201632w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiles for Antrodia cinnamomea Fruiting Bodies Harvested at Different Culture Ages and from Different Wood Substrates

Abstract: Antrodia cinnamomea is a precious edible fungus endemic to Taiwan that has long been used as a folk remedy for health promotion and for treating various diseases. In this study, an index of 13 representative metabolites from the ethanol extract of A. cinnamomea fruiting body was established for use in quality evaluation. Most of the index compounds selected, particularly the ergostane-type triterpenoids and polyacetylenes, possess good anti-inflammation activity. A comparison of the metabolite profiles of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 28 publications
(43 reference statements)
1
50
0
Order By: Relevance
“…The lanostane-type triterpenoids are produced in both mycelium and basidium, whereas ergostanes are related to basidiomatal formation and are produced only in basidium (6,14). Significantly, the ergostane production of A. cinnamomea growing on C. kanehirai Hayata is of higher efficiency and shows more compound variety than that growing on other trees (14,15). As to the metabolites of mycelium, lanostane-type triterpenoids and the derivatives of maleic acid, succinic acid and ubiquinone, have been reported (15).…”
mentioning
confidence: 99%
“…The lanostane-type triterpenoids are produced in both mycelium and basidium, whereas ergostanes are related to basidiomatal formation and are produced only in basidium (6,14). Significantly, the ergostane production of A. cinnamomea growing on C. kanehirai Hayata is of higher efficiency and shows more compound variety than that growing on other trees (14,15). As to the metabolites of mycelium, lanostane-type triterpenoids and the derivatives of maleic acid, succinic acid and ubiquinone, have been reported (15).…”
mentioning
confidence: 99%
“…Previously, Lin et al had reported the quantitative determination method of AC by HPLC with ultraviolet detection, requiring a long HPLC running time [17]. HPLC with mass spectrometry detection to evaluate the quality of AC mycelium was also conducted by Zhao and Leung, but the metabolite composition of the fruiting bodies of AC has not been evaluated [31].…”
Section: Resultsmentioning
confidence: 99%
“…Highperformance liquid chromatography (HPLC) with ultraviolet (UV) and photodiode array (PDA) detection methods has become a routine practice in some laboratories to quantify benzenoids and triterpenoids derivatives of fruiting body, mycelia, extract, and commercial preparation of AC [16][17][18][19]. These methods have played important roles in the quality control of AC and its commercial products.…”
Section: Introductionmentioning
confidence: 99%
“…C), there was almost no typical triterpenoids in the mycelial product. Lin et al argued that the presence of C. kanehirai was a necessary condition for the production of ergostan‐class triterpenoids in A. camphorata . Although there were no ergostan‐class triterpenoids in the mycelial product of A. camphorata produced by solid‐state fermentation in this study, several new active compounds were produced that may make compensate for the lack of fruiting body to a certain degree .…”
Section: Discussionmentioning
confidence: 99%